2017
DOI: 10.1177/0883911517751159
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine-loaded microcapsules fabricated by phase reversion emulsification-drying in liquid method: An evaluation of process parameters, characterization, and released properties

Abstract: Sinomenine is a natural alkaloid with important biological activities (e.g. anti-cancer, antiinflammatory, and anti-allergic). However, the unstability and short half-life absolutely limited its application to foods. Microencapsulation technology can offer a way to solve these issues. In this study, polylactic acid microcapsules loading sinomenine hydrochloride were fabricated by phase inversion emulsification-drying in liquid technique. The results showed that microcapsules had nice spherical shape, uniform p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In the same year, W. Zhang et al reported the benefits of SH polylactic acid microcapsules, which inhibited both bacteria and MDA-MB-231 cells. It (15.2 mM) exhibited a sustained release effect, a slower release rate, good biocompatibility, and no apparent cytotoxicity to normal L929 cells [ 46 ]. Concurrently, D. Zhang et al announced the radiosensitive effect of SH on cervical cancer cells.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…In the same year, W. Zhang et al reported the benefits of SH polylactic acid microcapsules, which inhibited both bacteria and MDA-MB-231 cells. It (15.2 mM) exhibited a sustained release effect, a slower release rate, good biocompatibility, and no apparent cytotoxicity to normal L929 cells [ 46 ]. Concurrently, D. Zhang et al announced the radiosensitive effect of SH on cervical cancer cells.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Then, the mold was compressed under 160 MPa for 5 min using a hydropress to obtain the tablets for in vitro release experiments. The release tests were performed in small cups containing 100 mL of pH 6.8 PBS with a rotation speed of 50 rpm using small paddles at 37 ± 0.5 °C for 6 h. At preset intervals (5,10,20,30,60,120,240, and 360 min), 1 mL of solution in each cup was extracted and replaced by equivoluminal fresh PBS. The acquired samples were filtered using polycarbonate filters (0.22 μm) and analyzed by UPLC.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…Multi-dose therapy with SIN-HCl leads to violent fluctuation of blood drug concentration, which may result in serious side effects. Although some sustained release strategies of SIN-HCl have been developed, the marketed SIN-HCl tablets still required administration twice per day, suggesting that novel and long sustained release strategies for SIN are needed. …”
Section: Introductionmentioning
confidence: 99%